THE INFLUENCE OF COORDINATION AND SUPERVISION ON THE EFFECTIVENESS OF EMPLOYEE WORK AT PT. HACACA CENTRAL LOGISTIC - Khasanah, Wasyatun; Soemadi, Rr Anggraini (JURNAL MUHAMMADIYAH MANAJEMEN BISNIS, 2025)
Examining how PT Hacaca Central Logistic's supervisors and coordinators affect workers' productivity is the primary goal of this research.  In this quantitative study, 83 participants were selected from among the staff at PT Hacaca Central Logistic.  Multiple linear regression was employed for data analysis.  Coordination improves productivity on the job, according to preliminary studies.  There is a positive and statistically significant relationship between partial research results supervision and job performance.  Concurrently, the efficacy of work is greatly impacted by supervision and coordination.  Coordination and supervision have an effect on the work effectiveness variable, according to the R Square value of the determination test, but other variables that were not considered had an effect on the remaining variables.  Based on these findings, it's clear that PT. Hacaca Central Logistic's workers could benefit greatly from better supervision and coordination in the workplace. Keywords: Coordination, Supervision, Work Effectiveness